Pemikiran Driyarkara Tentang Pendidikan dan Implikasinya Bagi Etika Pancasila - Restu Angga Permana (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This writing aims to explain and analyze Driyarkara's educational model, the role of Driyarkara's thinking in Indonesian education, and Driyarkara's efforts in realizing his point of view on education in Indonesia. The writing of this article uses the socio-historical method with the stages of verification, heuristics, interpretation, and historiography using a sociocultural approach and analytical descriptive writing. The results of this article explain that: (1) Driyarkara's educational model includes humanization, humanism, humanity, and humanism, (2) the role of Driyarkara's thinking in contributing to the nature of humanity in a complex manner through character building in educational institutions, 3) Efforts Driyarakara in realizing his point of view in expressing ideas in a book and implementing the realization of the application of character-based education in the field of education in order to create graduates with competent characters, compassion, and conscience. (4) An outline of Driyarkara's thoughts that are mutually sustainable and fundamentally related, including human characteristics, human morality, and conscience. (5) The ethical dimension of Driyarkara: Theological deontology. (6) The ethical implications of Pancasila from the Driyarkara perspective.